Chip-Scaled Ka-Band Photonic Linearly Chirped Microwave Waveform Generator - Brunetti, Giuseppe; Armenise, Mario N.; Ciminelli, Caterina (Frontiers in Physics, 2022)
Synthetic Aperture Radar (SAR) systems employ Linearly Chirped Microwave Waveform Generator (LCMWG) with large Time BandWidth Product (TBWP), to provide a wide range resolution. Photonics has now been recognized as a disruptive approach to achieve high performance at bandwidth of few tens of GHz, with light and compact architectures, due to the typical photonics benefits, as electromagnetic interference immunity, small power consumption, small footprint, high immunity to vibration/shock and radiation. In this paper, we report on the photonic generation of a high frequency LCMW, with a large TBWP (102 ÷ 103), using a chip-scaled architecture, based on a frequency-tuneable OptoElectronic Oscillator (OEO) and a Recirculating Phase Modulation Loop (RPML). A new configuration of the OEO employing an ultra-high Q-factor resonator, has been conceived to allow the oscillator working in Ka-band at 40 GHz or even more, with very low phase noise. Key building block of the RPML is a phase modulator driven by an engineered parabolic split waveform. Ultra-large Pulse Compression Rate (PCR) ≈ 104, together with large signal purity, were also obtained, making the proposed architecture particularly suitable for SAR systems with large range resolution demand, as for Earth surveillance and monitoring.